In vitro pharmaco-equivalence analysis of diclofenac potassium oral film-coated tablet relative to marketed generics - Omar Z. Ameer (GarVal Editorial Ltda., 2023)
Context: Diclofenac potassium, a potent member of the non-steroidal anti-inflammatory drugs (NSAIDs) that is commonly used for acute analgesia and multiple inflammatory conditions, has various marketed tablet brands available. However, quality parameters of tablet dosage forms may vary across different brands. Aims: To evaluate critical quality attributes, including in vitro dissolution characteristics of four diclofenac potassium immediate-release (IR) tablet brands (labeled A-D) collected from Saudi Arabia market. Methods: All brands were tested for conformity with the United States Pharmacopoeia, through evaluation of weight variation, hardness, friability, disintegration, and dissolution. Dissolution profiles were compared using model-dependent and-independent approaches relative to the innovator A. Results: Data showed that the samples were compliant in terms of weight variation, hardness and friability. Disintegration time (DT) for brands B and D was below USP specifications whereas that of brand C was higher. Brand B and D had higher dissolution efficiency (DE) and similar mean dissolution time (MDT) compared with innovator. Brand C had lower DE and greater MDT compared with innovator. Weibull model of drug-release kinetics was found to be the best fit for all samples. Conclusions: In summary, brand C, unlike brands B and D, appears to relatively undermine the purpose of a diclofenac IR formulation, given its longer DT, lower DE and slower dissolution release compared with the innovator. These differences are potentially attributable to variations in tablet additives and manufacturing processing across different pharmaceutical industries.